MANAGEMENT OF DEPRESSION IN TERMINALLY ILL PATIENTS – A CRITICAL REVIEW - O, Balaji; Bairy KL; N, Veena (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Depression is a well-recognized risk factor for shortened life span from cancer. Depression is among the main causes of disability in the world leading to increased suffering and mortality. As per research surveys over the years, prevalence among cancer patients varies widely from 3% to 38% for major depression and 1.5-52% for depression spectrum syndromes. The need of the hour is to effectively treat depression in cancer patients so that the quality of life can be improved and thereby patient survival. Both psychological and pharmacological interventions and the combination of both very much effective in treating depression in cancer patients. A broad range of therapies now exist, and the art of such therapy is the strategic selection of components from several models to best respond to the needs of the individual patient and his/her family in the specific circumstances, whether clinical, psychological, spiritual, or social. Â